1990
DOI: 10.1111/j.1745-4557.1990.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic Detection of Diacetyl in Orange Juice

Abstract: A GLC method was developed for detection of diacetyl(2,3-butanedione) and acetoin (3-hydroxy-2-butanone) in orange juice. Retention times for diacetyl and acetoin were 2.8 + 0.03 and 6.8 + 0.02 min, respectively. Concentration by distillation was essential to detect small quantities by GLC of diacetyl but was ineffective for acetoin. A linear response of diacetyl concentration to peak area was observed between 0.05 and 0.5 ppm. The peak areas at 0.05 and 0.5 ppm diacetyl were 1242 t 203 and 20142 ? 1120, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Diacetyl reacts comparatively faster than acetoin, and based on this property, diacetyl was determined successfully in presence of acetoin [ 8 , 10 , 11 ]. Later, when GC was introduced, it became the most frequently used method for diacetyl determination [ 12 14 ], and sometimes HPLC is also used [ 15 ]. By virtue of high sensitivity and the strong spatial resolution of fluorescence measurements, much interest has been shown in pre-column fluorescent derivatization methods in chromatography [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diacetyl reacts comparatively faster than acetoin, and based on this property, diacetyl was determined successfully in presence of acetoin [ 8 , 10 , 11 ]. Later, when GC was introduced, it became the most frequently used method for diacetyl determination [ 12 14 ], and sometimes HPLC is also used [ 15 ]. By virtue of high sensitivity and the strong spatial resolution of fluorescence measurements, much interest has been shown in pre-column fluorescent derivatization methods in chromatography [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This shows that D-erythrulose reductase also plays an important role in the liver. Dicarbonyl compounds such as diacetyl, a good substrate of the enzyme, are present in many everyday foods and beverages, such as alcoholic drinks (9, JO), milk (11), butter (12), buttermilk (13), cheese (14,15), and orange juice (16). Borders and Riordan reported that about 1 mM diacetyl modified arginine residues in proteins (17), which suggests that a high concentration of diacetyl may be toxic for animals.…”
Section: Substrate Specificity Of D-erythrulose Reductase-mentioning
confidence: 99%
“…Due to their widespread use in a variety of applications, in the recent years timeconsuming, complex, and expensive traditional techniques have been substituted by these types of sensors. It has been especially evident in the field of volatile organic compound (VOC) detection, where traditional techniques, such as chromatography-mass spectrometry [18][19][20][21], generally lack ease of use, need specialized personnel and elaborate protocols, and are characterized by high cost of the devices and insufficient flexibility. When early warning and quality monitoring applications are requested, resistive sensors are valuable alternatives.…”
Section: Introductionmentioning
confidence: 99%